2021
DOI: 10.3892/etm.2021.10257
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib ameliorates diabetic neuropathy by decreasing apoptosis and oxidative stress in dorsal root ganglion neurons via the miR‑155/COX‑2 axis

Abstract: Celecoxib (CXB) is the only clinical cyclooxygenase-2 (COX-2) inhibitor. Oral administration of CXB in experimental diabetic mice effectively relieved the symptoms of diabetic neuropathy (DN); however, the molecular mechanism remains unclear. The present study aimed to investigate the potential molecular mechanisms of CXB in the treatment of DN. An in vitro cellular model of DN was produced by stimulating dorsal root ganglion (DRG) neurons with high glucose. Cell viability and apoptosis were assessed by Cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Abdulaziz A Alzahrani demonstrated that β-adrenoceptor blockade propranolol decreased respiratory frequency and abolished the CIH-mediated increase in vascular sympathetic nerve density. Similarly, several studies have shown that cyclooxygenase inhibitors can attenuate inflammatory responses by decreasing oxidative stress ( Cheng et al, 2021 ). For example, Tissot Low showed that IH-induced lung inflammation could be completely abolished by daily intraperitoneal injection of ibuprofen (a cyclooxygenase inhibitor) ( Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdulaziz A Alzahrani demonstrated that β-adrenoceptor blockade propranolol decreased respiratory frequency and abolished the CIH-mediated increase in vascular sympathetic nerve density. Similarly, several studies have shown that cyclooxygenase inhibitors can attenuate inflammatory responses by decreasing oxidative stress ( Cheng et al, 2021 ). For example, Tissot Low showed that IH-induced lung inflammation could be completely abolished by daily intraperitoneal injection of ibuprofen (a cyclooxygenase inhibitor) ( Cheng et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, several studies have shown that cyclooxygenase inhibitors can attenuate inflammatory responses by decreasing oxidative stress ( Cheng et al, 2021 ). For example, Tissot Low showed that IH-induced lung inflammation could be completely abolished by daily intraperitoneal injection of ibuprofen (a cyclooxygenase inhibitor) ( Cheng et al, 2021 ). Therefore, we speculate that cyclooxygenase inhibitors can improve OSA by inhibiting oxidative stress which needs to be demonstrated experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…IL-1β and CXB might change ROS catalysis of the superoxide dismutase (SOD) to a different exent in the cytosol and mitochondira, and result in a discrepancy between consequent intracellular and mitochondrial ROS [ 33 , 34 ]. It was found that CXB affects ROS production variably in several studies, and altered mitochondrial function in a different context should be responsible for the difference [ 35 , 36 ]. Mitochondria are the primary sources of ROS, while pathological factors such as inflammation and hypoxia affect complex II of the mitochondrial respiratory chain and NADPH oxidase (NOX) activity.…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that overactive matrix metalloproteinases (MMP) induced by IL-1β lead to the structural change of intervertebral discs [26]. Furthermore, IL-1β promotes blood vessel and nerve ingrowth, followed by leukocyte infiltration and pain (35). In addition to IL-1β, other inflammatory cytokines including IL-6, IL-17, and TNF were also characterized in IDD.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding showed celecoxib to down-regulate the hippocampal COX-2 expression and up-regulate the BDNF-TrkB pathway to reverse memory deficits in a diabetic rat model [ 80 ]. In addition to that, celecoxib was found to ameliorate diabetic neuropathy via the inhibition of oxidative stress and apoptosis through the modulation of miR-155 in dorsal root ganglion neurons [ 81 ].…”
Section: The Quest Of Repurposing and Efforts From Medicinal Chemistsmentioning
confidence: 99%